The Effects of System Quality, Information Quality, and Management Support of the E-Performance System on Civil Servant Performance Measurement in Regional Government Organizations - Vivi Oktari; Sofyan Ashari Nur (Jurnal Akuntansi, 2026)
Digital transformation in the public sector has accelerated the implementation of E-Performance systems as a strategic instrument for enhancing the objectivity, transparency, and accountability of civil servant performance measurement. Despite their widespread adoption within regional government institutions, the effectiveness of these systems remains dependent on several critical information system success factors. This study aims to examine the effects of system quality, information quality, and management support on employee performance measurement in Regional Government Organizations (Organisasi Perangkat Daerah/OPD). A quantitative approach with an associative research design was employed. Primary data were collected through questionnaires distributed to 76 civil servants who actively use the E-Performance system and were selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS version 27 following validity, reliability, and classical assumption tests. The findings indicate that system quality has a positive and statistically significant effect on employee performance measurement. In contrast, information quality and management support do not significantly influence employee performance measurement. Furthermore, the simultaneous test reveals that the three independent variables do not collectively have a significant effect on employee performance measurement. The adjusted coefficient of determination (Adjusted R²) is 9.7%, indicating that the majority of the variation in employee performance measurement is explained by factors beyond the proposed research model. These findings suggest that improving the technical quality of the E-Performance system alone is insufficient to enhance employee performance measurement. Greater attention should also be given to organizational and human resource factors to maximize the effectiveness of digital performance management in regional government institutions.